An Analysis of Grammatical Errors Committed by Students in Writing Argumentative Paragraph - Lestari, Ni Putu Candra Widiya; Ramendra, Dewa Putu; Utami, Ida Ayu Made Istri (Universitas Pendidikan Ganesha, 2023)
Writing skills are very important for students to master to help them prepare for their future. However, grammar is one of the obstacles for students in writing English. This research aims to analyze grammatical errors made by students in writing argumentative paragraphs and to analyze the sources of these errors. Second semester English Language Education students were chosen as the subjects of this research. Furthermore, in analyzing the data, this research applies a combination of descriptive qualitative and descriptive quantitative methods. Apart from that, data was collected through collecting documents from the end-of-semester tests. The data analysis procedure consists of three specific steps, namely data reduction, data presentation, and drawing conclusions/verification. The results of the research found that students made 11 types of errors with a total of 165 errors. Most of them made omission of article errors with 39 (23.63%) errors, then simple addition 33 (20%) errors, alternating form 27 (16.36%) errors, omission of to be 21 (12.72%) errors, then omission of preposition 17 (10.30%) errors, omission of plural –s with 15 (9.09%) errors, misordering 6 (3.63%) errors, regularization 3 (1.81%) errors, and finally double marking and archi-form each 1 ( 0.60%) error. In addition, sources of errors were found in four types: interlingual transfer, intralingual transfer, context of learning, and communication strategy. The majority of students made mistakes due to intralingual transfer, 119 (72.12%) errors were found, followed by interlingual transfer 41 (24.84%) errors, communication strategy 3 (1.81%), and context of learning 2 (1.21%) errors.